2005
DOI: 10.1097/01.qco.0000168382.86024.14
|View full text |Cite
|
Sign up to set email alerts
|

The role of type-specific antibodies in colonization and infection by Helicobacter pylori

Abstract: This review highlights the recent advances in our understanding of how antibodies may influence the development of gastric inflammation and bacterial colonization. Such information can significantly increase our basic knowledge of immune regulation and protection against H. pylori infection, but can also indicate new strategies for vaccine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…8 The increased risk of stomach cancer suggests that local gastrointestinal effects associated with PID, such as the decreased production of gastric IgA and hydrochloric acid, may facilitate Helicobacter pylori colonization and gastric inflammation and promote carcinogenesis. Although there is mixed support for such a pathogenic mechanism, [32][33][34][35] and the role for cofactors such as alterations in the p53 gene are yet to be clarified, 36 these data support the regular use of diagnostic tests and treatment of H pylori infection in adults with PID, together with endoscopic follow-up of those with premalignant gastric lesions. 37 We observed a large excess risk for thymoma on the basis of 2 cases occurring in patients with CVID.…”
Section: Discussionmentioning
confidence: 88%
“…8 The increased risk of stomach cancer suggests that local gastrointestinal effects associated with PID, such as the decreased production of gastric IgA and hydrochloric acid, may facilitate Helicobacter pylori colonization and gastric inflammation and promote carcinogenesis. Although there is mixed support for such a pathogenic mechanism, [32][33][34][35] and the role for cofactors such as alterations in the p53 gene are yet to be clarified, 36 these data support the regular use of diagnostic tests and treatment of H pylori infection in adults with PID, together with endoscopic follow-up of those with premalignant gastric lesions. 37 We observed a large excess risk for thymoma on the basis of 2 cases occurring in patients with CVID.…”
Section: Discussionmentioning
confidence: 88%
“…5 This is an observation that has been contested by Akhiani who suggested that antibodies are not only dispensable for protection, but they impair both the elimination of bacteria and the development of gastritis. 1 This effect appears to be IgA-dependent and is not a function of specific IgM or IgG antibodies. Therefore, the contention that IgA antibodies are irrelevant in the pathogenesis remains in doubt.…”
Section: Methodsmentioning
confidence: 97%
“…After clearance, H. pylori reinfection can occur readily even in the face of a robust antibody response (1,26,31,41). It has been shown that vaccination through a mucosal route can provide long-term protection against other pathogens (19,23,27,33).…”
Section: Discussionmentioning
confidence: 99%